2015
DOI: 10.1111/aos.12778
|View full text |Cite
|
Sign up to set email alerts
|

Morning Glory Disc Anomaly in childhood – a population‐based study

Abstract: ABSTRACT.Purpose: To report prevalence, ocular characteristics and coexisting neurological, behavioural, somatic and neuroradiological abnormalities in children and adolescents with morning glory disc anomaly (MGDA). Methods: In a cross-sectional population-based study, 12 patients with MGDA, aged 2-20 years, were identified. All 12 agreed to ophthalmological assessments including visual functions, refraction, fundus photography, optical coherence tomography (OCT) and ocular motor score (OMS). Neurological exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 28 publications
0
36
0
6
Order By: Relevance
“…2,3,6 Extraorbital abnormalities were also reported, including a wide spectrum of vascular abnormalities, 7 posterior pituitary ectopia, 8 midline facial defects, basal encephalocele, 9 and abnormalities of the visual pathways too, the latter consistent with our observation of optic nerve/chiasm thickening. 2,10,11 Ceynowa et al 10 and Ellika et al 2 reported one case each of bulging of the prechiasmatic segment of the ipsilateral optic nerve, without specifying if gadolinium enhancement was present at that site, and referred these features to a probable optic nerve glioma. Bandopadhayay et al 11 described similar findings, further characterized by thin peripheral enhancement, interpreted again as optic glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,6 Extraorbital abnormalities were also reported, including a wide spectrum of vascular abnormalities, 7 posterior pituitary ectopia, 8 midline facial defects, basal encephalocele, 9 and abnormalities of the visual pathways too, the latter consistent with our observation of optic nerve/chiasm thickening. 2,10,11 Ceynowa et al 10 and Ellika et al 2 reported one case each of bulging of the prechiasmatic segment of the ipsilateral optic nerve, without specifying if gadolinium enhancement was present at that site, and referred these features to a probable optic nerve glioma. Bandopadhayay et al 11 described similar findings, further characterized by thin peripheral enhancement, interpreted again as optic glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Among Ceynowa et al case series, another patient with asymmetric optic chiasm was reported: the authors attributed this aspect to an atrophy contralateral to MGDA, explaining it as an anterograde degeneration process from ganglion cell deficit within the developing retina. 10 No images were available for the check, but the fact that ipsilateral optic nerve and contralateral optic tract, with respect to MGDA site, were not described as atrophic too, make us suspect that the asymmetry should be better interpreted as thickening on the affected side, rather than atrophy on the contralateral one. We believe that also the case described by Auber and O'Hara 2 should be considered in the same way: they describe a reduction in the size of the optic nerve and chiasm contralateral to MGDA which, in our opinion, cannot be explained by an anterograde degeneration as suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Zentral zeigt sich eine gliöse Auflagerung. Die Sehschärfe des betroffenen Auges (bilaterale Fälle sind selten) ist in der Regel mäßig bis stark reduziert (11). Bei ca.…”
Section: Grubenpapillenunclassified
“…Zentral lässt sich i. d. R. eine typische büschelförmige gliöse Auflagerung am Papillengrund darstellen. Die OCT-Untersuchung ist weiterhin hilfreich zur Aufdeckung einer begleitenden serösen Makulaabhebung, einer Makulaaplasie oder einer Einbeziehung der Makula in den Papillenbereich (macular capture) [20,21] (▶ Abb. 2).…”
Section: Morning-glory-papilleunclassified